Analysis of the Pedagogic Competency of Islamic Religious Education Teachers in Improving the Quality of Learning at SMP Negeri 2 Labuan - Rumuat, Nanda Apriani; Rusli Takunas; Basire, Jumri Hi. Tahang (Al-Tawjih: Jurnal Pendidikan Islam, 2025)
This research is motivated by the importance of pedagogic competence of Islamic Religious Education teachers in improving the quality of learning in schools. Teachers’ pedagogic competence has a great influence on the learning process because it is related to the teacher’s ability to understand students, plan learning, carry out learning, and evaluate learning. This study aims to determine the pedagogic competence of Islamic Religious Education teachers and teachers’ efforts in improving the quality of learning at SMP Negeri 2 Labuan. This study uses a qualitative approach with a descriptive type of research. Data collection techniques are carried out through observation, interviews, and documentation. The research informants consisted of school principals, Islamic Religious Education teachers, and students. Data is analyzed through data reduction, data presentation, and conclusion drawn. The results of the study show that the pedagogic competence of Islamic Religious Education teachers at SMP Negeri 2 Labuan is quite good. This can be seen from the teacher’s ability to understand the characteristics of students, prepare learning plans, use varied learning methods, and manage learning actively and communicatively. Teachers also use simple language and relate the material to the students’ daily lives to make it easier to understand. In addition, teachers make various efforts to improve the quality of learning, such as compiling lesson plans, using lecture methods, questions and answers, discussions, and direct practice, and providing motivation to students. However, there are still several obstacles, such as the limitation of learning media and the lack of activeness of some students in the learning process. The conclusion of this study is that the pedagogic competence of Islamic Religious Education teachers has an important role in improving the quality of learning at SMP Negeri 2 Labuan. Good pedagogic competence helps teachers create more active, effective, and meaningful learning for students.